Welcome home : life on the new planet earth - Rother, Steve; The Group (Spirits) (Poway, Ca. : Lightworker, 2002)
"The world we knew is rapidly evolving. Life on planet earth is becoming increasingly unpredictable. The old rules no longer function. According to 'the Group', these changes have greater implications than we imagine. As unexpected as recent events have been, they merely mark the beginning. The evolution of mankind has begun. The Group's purpose is to prepare us for what lies ahead. In 'Welcome home', they offer us keys to unlocking secrets of developing our full powers as creators and using them in our lives now."--Cover, p. 4.
"Includes the very latest information about the Crystal Children."--Cover.
"The more your awareness grows... The important this book will become."--Cover.
Keywords: New Age movement; Spiritual life -- New Age movement; Self-actualization (Psychology); Channeling (Spiritualism)